Progress in Superlubricity Across Different Media and Material Systems—A Review - Ayyagari, Aditya; Alam, Kazi Istiaque; Berman, Diana; Erdemir, Ali (Frontiers in Mechanical Engineering, 2022)
Superlubricity is a terminology often used to describe a sliding regime in which the adhesion leading to friction or resistance to sliding literally vanishes. For improved energy security, environmental sustainability, and a decarbonized economy, achieving superlubric sliding surfaces in moving mechanical systems sounds very exciting, since friction adversely impacts the efficiency, durability, and environmental compatibility of many moving mechanical systems used in industrial sectors. Accordingly, scientists and engineers have been exploring new ways to achieve macroscale superlubricity through the use of advanced materials, coatings, and lubricants for many years. As a result of such concerted efforts, recent developments indicate that with the use of the right kinds of solids, liquids, and gases on or in the vicinity of sliding contact interfaces, one can indeed achieve friction coefficients well below 0.01. The friction coefficient below this threshold is commonly termed the superlubric sliding regime. Hopefully, these developments will foster further research in the field of superlubricity and will ultimately give rise to the industrial scale realization of nearly-frictionless mechanical systems consuming far less energy and causing much-reduced greenhouse gas emissions. This will ultimately have a substantial positive impact on the realization of economically and environmentally viable industrial practices supporting a decarbonized energy future. In this paper, we will provide an overview of recent progress in superlubricity research involving solid, liquid, and gaseous media and discuss the prospects for achieving superlubricity in engineering applications leading to greater efficiency, durability, environmental quality, and hence global sustainability.